Advanced downhole geophysical monitoring of subsurface changes with fibre-optic sensors. - Sidenko, Evgenii (Curtin University, 2022)
Field experiments and modelling show that the use of free-surface multiples can significantly improve the coverage of the vertical seismic profiling with downhole distributed acoustic sensors. Field studies also show that these sensors can record natural noise and human activity, and indicate imperfections of borehole cementation. The signal recorded by these sensors shows excellent correlation with reservoir pressure and temperature, which can be used for monitoring of CO2 injection into geological formations.